(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Unlike India where Article 19(1)(a) of the constitution ensures freedom of speech to all citizens, in England freedom of speech including freedom of press has been guaranteed by the court decisions and various legislations from time to time.